ANALYSIS OF FACTORS INFLUENCING CLEAN AND HEALTHY (CHLB) PRACTICES TO PREVENT PULMONARY TB AMONG STUDENTS AT ISLAMIC BOARDING SCHOOL PALEMBANG - Hendawati; Intan Kumalasari; Irmawartini; Lindawati (Indonesia Epidemiological Journal, 2025)
Background: Indonesia ranks second globally for tuberculosis (TB) cases, with 1,060,000 cases and 134,000 deaths annually. This results in 17 deaths every hour. Clean and Healthy Living Behavior (CHLB) is crucial in preventing pulmonary TB. In Islamic boarding schools (pesantren), the risk of TB may rise if students neglect hygiene. Therefore, it is important to analyze factors influencing CHLB practices for preventing TB among students at Zaadul Ma'ad Islamic Boarding School. Purpose: This study aims to analyze the factors influencing CHLB practices to prevent pulmonary TB among students at Zaadul Ma'ad Islamic Boarding School, identifying key factors to improve hygiene practices and reduce TB transmission. Methods: A quantitative, cross-sectional approach was used with 50 respondents selected via total sampling. A structured questionnaire was employed, and data were analyzed through univariate, bivariate (chi-square test at 95% significance), and multivariate analyses. Results: All respondents were male, with 86% in mid-adolescence (15-17 years). 70% had normal nutritional status, and 35% had a history of smoking. Significant factors related to CHLB practices included knowledge, attitudes, facility and resource availability, and support from stakeholders. Attitudes (OR=11.374) and school regulations (OR=9.409) were the most influential factors. Conclusion: Islamic boarding schools should implement regulations mandating personal hygiene and provide guidelines for cleanliness to promote better CHLB practices, preventing TB spread.